2019
DOI: 10.1111/joms.12531
|View full text |Cite
|
Sign up to set email alerts
|

60 Years of March and Simon’s Organizations: An Empirical Examination of its Impact and Influence on Subsequent Research

Abstract: We provide an analytic and systematic review of the impact of March and Simon’s seminal Organizations on management research and discuss the book’s value for current research and propose future applications of it. Building on bibliometric and text‐mining approaches, our empirical analysis reveals that although Organizations was contextually based in the industrial milieu of the 1950s, its concepts have found ongoing resonance with scholars. Further, we find that much of this resonance appears to be driven by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 222 publications
(209 reference statements)
0
18
0
1
Order By: Relevance
“…The year 1998 coincides with the publication of Van Dyne and LePine (1998), which is the most cited paper in our data set, and that several studies are considered as the foundation study for the field (Barnett, Henriques, & Husted, 2020;Danvila-del-Valle, Estévez-Mendoza, & Lara, 2019). Having identified the first turning point, we followed the established methodological prescription of dividing in equal timeframes of 10 years each (Barnett, Henriques, & Husted, 2020;Castillo-Vergara, Alvarez-Marin, & Placencio-Hidalgo, 2018;Wilden, Hohberger, Devinney, & Lumineau, 2019). The bibliometric analyses were then performed separately for each period with the software VOSviewer following Van Eck and Waltman (2014).…”
Section: Description Of the Bibliometric Analysesmentioning
confidence: 99%
“…The year 1998 coincides with the publication of Van Dyne and LePine (1998), which is the most cited paper in our data set, and that several studies are considered as the foundation study for the field (Barnett, Henriques, & Husted, 2020;Danvila-del-Valle, Estévez-Mendoza, & Lara, 2019). Having identified the first turning point, we followed the established methodological prescription of dividing in equal timeframes of 10 years each (Barnett, Henriques, & Husted, 2020;Castillo-Vergara, Alvarez-Marin, & Placencio-Hidalgo, 2018;Wilden, Hohberger, Devinney, & Lumineau, 2019). The bibliometric analyses were then performed separately for each period with the software VOSviewer following Van Eck and Waltman (2014).…”
Section: Description Of the Bibliometric Analysesmentioning
confidence: 99%
“…Dada su importancia, en este trabajo se realiza una explicación más detallada del mismo. Como subrayan Wilden et al (2019), March y Simon (1958) han tenido una influencia trascendental en el conocimiento académico y un número creciente de investigaciones está volviendo a sus conceptos centrales en busca de inspiración para facilitar y mejorar su propio trabajo en una gran variedad de disciplinas científicas, por ejemplo, la gestión de los RR. HH.…”
Section: Implicaciones Teóricas Y Prácticasunclassified
“…Wilden et al () use a text‐mining approach of the abstracts of peer‐reviewed articles identified as having cited Organizations . They address how the book influenced research during four time periods covering 1957 to 2017.…”
Section: Presentation Of Papersmentioning
confidence: 99%